ENVIRONMENTAL FACTORS AFFECTING FINANCIAL PERFORMANCE DURING THE COVID-19 PANDEMIC IN ASEAN: SOCIAL DISCLOSURE AS MODERATING - Yohanes Mardinata Rusli (Universitas Agung Podomoro, 2022)
This study discusses the factors of environmental performance, environmental disclosure, and corporate social disclosure that affect corporate financial performance. The current global warming is worrying enough that the country's leaders are committed to reducing the level of carbon emissions in each country. Environmental disclosures and social disclosures that must exist during the COVID-19 pandemic have not been implemented due to large-scale social restriction regulations from the government, so they cannot be disclosed. The research subject is a mining company in one of the largest ASEAN countries, namely Indonesia. Meanwhile, the object of this research is the Annual Report and Sustainability Report for the period 2018-2021 published on each ASEAN country's Stock Exchanges website. The study results show that Environmental Disclosure significantly influences the Financial Performance of mining companies listed on the IDX in 2018-2020